Penerapan Media Pembelajaran Kartu Huruf Dalam Meningkatkan Perkembangan Kognitif Pada Anak Usia Dini Di Ra As-Syarif - Beby Melati; Cahaya Cahaya; Winda Wahyuni; Trini Dama Yanti (Institut Teknologi dan Bisnis Semarang, 2024)
The importance of learning media in increasing children's enthusiasm for learning or using learning media will make it easier for an educator to provide learning to young children. Using learning media will not only stimulate cognitive development in children, but will stimulate all aspects of development in early childhood. Researchers carried out research at RA As-Syarif Sibanggor Jae. This research aims to see how early childhood cognitive development develops through games using letter cards as media. This research uses a qualitative method with a descriptive approach. The research results include qualitative data which suggests that 1) It is very important to align cognitive development with the golden age because the golden age occurs in the first five years of a child's life. Therefore, the cognitive learning process is very important and effective if carried out through games; 2) Early childhood cognitive development is still in the pre-functional stage, so they are not yet able to think abstractly in learning that requires media; 3) Playing with letters, looking for letters using cards, and asking children questions during the activity. With this method, children learn to recognize and understand letters.